Transforming Education: The Role of Transformational Leadership in Elevating High School Quality - Rudolf Kempa; Arnold Sahalessy; Johanna Matitaputty (STAI Hubbulwathan Duri, 2025)
This study explores the influence of principal leadership on educational administration and teacher performance at State Senior High School 6 Ambon. Ineffective leadership often leads to a demotivating work environment, negatively affecting both teacher performance and student outcomes. A qualitative research design was employed, utilizing observations, interviews, and document analysis to gather data. The study focused on the principal’s role in cultivating a supportive environment, managing resources effectively, and fostering teacher development through training, workshops, and socialization initiatives. The findings reveal that strong, proactive leadership significantly improves both educational administration and teacher performance. The principal’s consistent support for professional development initiatives has led to increased teacher motivation and instructional effectiveness. This, in turn, positively impacts student learning outcomes. The study underscores the importance of leadership in shaping the educational climate. A principal who provides guidance, resources, and growth opportunities plays a pivotal role in enhancing school performance. Effective and supportive principal leadership is crucial for strengthening educational administration and improving teacher effectiveness. The results suggest that educational policymakers and stakeholders should invest in leadership development programs to empower school leaders with the skills needed to drive institutional improvement. Such initiatives can lead to meaningful changes that benefit both teachers and students.